Prevalence and Susceptibility Pattern of Enterococcus spp in Clinical Samples: A Retrospective Study From a Tertiary Care Teaching Hospital in an Eastern Indian State - Diptimayee Rout; subhalaxmi bhattacharya; priyadarhini bhoi; kundan sahu; nihar panda; sarita otta (Al-Anbar Medical Journal)
Background: Enterococcus, a low virulent yet hardy organism, is a cause of many community acquired as well as nosocomial infections. Antibiotic resistance in Enterococcus spp. is rising worldwide owing to their intrinsic resistance to multiple drugs. The combination therapy of beta-lactam antibiotics with aminoglycosides is the choice of treatment for this type of infection. But this is often rendered ineffective on account of high-level aminoglycoside resistance. Vancomycin resistance further complicates the scenario.Objectives: To note the predominant infections caused by Enterococcus spp. and to show their resistance pattern, with particular emphasis on vancomycin resistance.Materials and Methods: This study was conducted retrospectively in our tertiary care teaching hospital in Odisha, Eastern India, where 200 consecutive, nonrepetitive Enterococcus spp obtained on culture were included. Their demographic profile was collected from the lab register, and analysis was done using MS Excel.Results: The commonest sample from which Enterococcus spp was isolated was urine (n = 82, 41%), followed by blood (n = 49, 24.5%). E. faecalis (n = 120, 60 %) followed by E. faecium (n = 55, 27.5 %) were the most common species seen. Flouroquinolones, macrolides, and tetracycline were the most resistant antibiotics for all the Enterococcus species. E. faecalis had a much higher percentage of susceptibility to penicillin and higher level gentamicin (76.5% and 55.6%, respectively) compared to E. faecium (10.7% and 13.2%, respectively). Among the total, 43 (21.5%) isolates were vancomycin resistant, and only 3 (1.5%) showed moderate susceptibility. All the isolates 200 (100%) were tigecycline susceptible.Conclusion: The present study highlights increased vancomycin resistance as noted in 21.5% Enterococcus isolates. Quinolones, macrolides, and tetracycline showed better sensitivity to VRE, probably owing to lesser use in clinical scenarios. Urinary tract infection is the predominant infection caused by Enterococcus spp. Nitrofurantoin is an effective drug, particularly for E. faecalis.